Characterization of exosomal microRNAs in preterm infants fed with breast milk and infant formula - Kim, Eun-Bit; Song, Jun Hwan; Le, Linh Nguy-Hoang; Kim, Ho; Koh, Ji Won; Seo, Yekyeng; Jeong, Hwal Rim; Kim, Hyun-Taek; Ryu, Seongho (Frontiers in Nutrition, 2024)
Breastfeeding not only reduces infection-related morbidity, but also increases growth of preterm infants. Advantages of breast milk (BM) for preterm infants are significant. They continue to be studied. However, because not all preterm infants can receive breastfeeding, bovine-based infant formula (IF) is used as an alternative, which may increase the risk of several preterm complications. Exosomes isolated from biofluids are emerging as biomarkers in research of various diseases. Here, we characterized miRNA contents of exosomes in urine and serum samples of preterm infants who were BM and IF fed and performed transcriptomic analysis of small RNA libraries. We identified significantly up-regulated 6 miRNAs and 10 miRNAs, respectively. Gene Ontology (GO) analysis revealed that target genes of these miRNAs might participate in neuronal development, immunity modulation, detoxification of reactive oxygen species, and transmembrane exchange. Our data suggest that exosome-based systemic screening for preterm infants with breastfeeding might be a screening tool for identifying target molecules involved in therapy for preterm infants in neonatal intensive care unit (NICU) and for future application as nutraceutical formulations or pharmaceuticals.Value are expressed as mean±standard deviation or number (%).Abbreviations: SGA, small for gestational age * The case of both Maternal diabetes and Materanl hypertension (n=3 in Breast-fed and n=4 in Formula-fed).